Building The Event in the (AlBansion) Novel - Alyammahi, Shaimaa; Bouali, Abderrahman; Alhashemi, Badeeah (Al-Adab Journal, 2024)
Making the event in the novel is not an easy matter for the writer, as it requires intelligence, sophistication, and literary prowess in arranging it according to a special system that attracts the recipient to him and draws him to the story and makes him interact and anticipate with the events. Motivated to continue reading, and the success of the novel is linked to the success of the writer's ability to formulate events and put them in an appropriate, coherent, and logical template.This study seeks to shed light on the construction of the event in the (Al Bansion) novel by the novelist Abdullah Al-Nuaimi, benefiting from the data of the descriptive analytical approach. The research begins with an introduction to the events of the novel, then a theoretical material in which we show the nature and importance of the fictional event, also we study the types of formats used in constructing the event in the novel, and we will follow the structuring of the event construction by analyzing the beginning of the novel, the plot, and finally the conclusion of the novel.